2016
DOI: 10.1002/ppul.23444
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional lung function in cystic fibrosis measured by electrical impedance tomography

Abstract: EIT changes during forced expiration correlate with lung function parameters, clinical findings, and radiology. Regional analysis of EIT illustrates regional lung function and visualizes individual therapeutic effects. Pediatr Pulmonol. 2016;51:1191-1199. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 31 publications
(50 reference statements)
1
31
0
Order By: Relevance
“…Our earlier study on healthy adults showed a good correlation between EIT and spirometric pneumotachography measurements in volume, but a small deviation in flow during forced expiration maneuvers . Also in the present study, there was good correlation between spirometry and EIT for the asthmatic patients and controls ( P < 0.001 for FEV 1 , FEV 0.5 , MEF 75 , MEF 50 , and MEF 25 in all groups, except P = 0.0038, for MEF 75 in the asthmatics before BSL).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our earlier study on healthy adults showed a good correlation between EIT and spirometric pneumotachography measurements in volume, but a small deviation in flow during forced expiration maneuvers . Also in the present study, there was good correlation between spirometry and EIT for the asthmatic patients and controls ( P < 0.001 for FEV 1 , FEV 0.5 , MEF 75 , MEF 50 , and MEF 25 in all groups, except P = 0.0038, for MEF 75 in the asthmatics before BSL).…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, a scaling between these two data were required. In an earlier study in healthy adults, we showed that spirometric volumes Vspirotrue(ttrue) and impedance changes ΔnormalZglobaltrue(normalttrue) correlate well during spontaneous breathing and forced expiration maneuvers . In detail, this is described as: Vspirotrue(ttrue)=a*ΔZglobaltrue(ttrue)+b, where “a” is the scaling factor from arbitrary unit [AU] to liter [L] and “b” corresponds to a shift of the ordinate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is one of the largest EIT studies involving human subjects for the determination of regional lung function ever performed. The few previous studies on paediatric patients are limited to 10‐20 patients; healthy children were hardly ever studied …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies [1], [2] show that EIT can facilitate real time dynamic monitoring of lung aeration and improve the breathing control of both children and preterm babies by indicating areas of lung that are subject to over inflation or lung collapse. Currently, especially for preterm babies, there is no monitoring device available to detect and give early warning of respiratory failure.…”
Section: Introductionmentioning
confidence: 99%